2018
DOI: 10.3389/fcimb.2018.00272
|View full text |Cite
|
Sign up to set email alerts
|

Is IL-1β Further Evidence for the Role of Propionibacterium acnes in Degenerative Disc Disease? Lessons From the Study of the Inflammatory Skin Condition Acne Vulgaris

Abstract: The pathogenesis of degenerative disc disease is a complex and multifactorial process in which genetics, mechanical trauma, altered loading and nutrition present significant etiological factors. Infection of the intervertebral disc with the anaerobic bacterium Propionibacterium acnes is now also emerging as a potentially new etiological factor. This human commensal bacterium is well known for its long association with the inflammatory skin condition acne vulgaris. A key component of inflammatory responses to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Because correlations among clinical symptoms, radiological signs of disc degeneration, and treatment outcomes are not satisfactory, the selection of treatment options is difficult and the options employed often yield less than satisfactory results. Clearly, a more detailed understanding of the causes and development of DDD is needed so patients can be stratified for tailored or personalized treatments where possible (21). IDD advancing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because correlations among clinical symptoms, radiological signs of disc degeneration, and treatment outcomes are not satisfactory, the selection of treatment options is difficult and the options employed often yield less than satisfactory results. Clearly, a more detailed understanding of the causes and development of DDD is needed so patients can be stratified for tailored or personalized treatments where possible (21). IDD advancing.…”
Section: Discussionmentioning
confidence: 99%
“…The infection may therefore result in local tissue inflammation with edema, and due to production of cytokines known to affect the bone; this is leading to MC type 1 in the vertebral endplates and subchondral bone marrow (26). The identification of Propionibacterium acnes biofilms in intervertebral disc tissue obtained from patients who have undergone microdiscectomy, combined with previous studies demonstrating the success of antibiotic treatment for patients with CLBP , has led to the suggestion that P. acnes infection of the intervertebral disc may be another important causative factor for the development of DDD (21). Ozone (O3) gas, discovered in the mid-nineteenth century, is a molecule consisting of three atoms of oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our data It should furthermore be noted that the high data variability within the two degeneration groups for all targets indicates that HYAL expression and activity is not only affected by the grade of degeneration, but also by other factors that were not controlled for due to the small sample size. Possible examples include, but are not limited to, diabetic conditions [48], P. acnes infection [49] and tissue loading patterns [50,51]. Higher number of samples will be needed to better identify trends and statistically significant differences in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been a point of controversy as to whether they are true infections or intraoperative contamination, due to these bacteria are skin colonizing bacteria and the most common pathogens of implant-associated infections in the beginning. However, recent evidence suggested that bacteria are present in the disc before acquisition of disc tissue [ 4 ]. The detection of bacteria in degenerated cervical IVDs has been discussed in our study previously, and both bacteria were found to be predominant, but S. epidermidis was more common than P. acnes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%